2010
DOI: 10.3892/ol_00000114
|View full text |Cite
|
Sign up to set email alerts
|

Small-interfering RNA-mediated silencing of the MAPK p42 gene induces dual effects in HeLa cells

Abstract: Abstract. The genesis and progression of cervical cancer involve the mutation or deviant expression of numerous genes, including the activation of oncogenes (Ha-ras, C-myc, C-erbB2 and Bcl-2) and inactivation of tumor-suppressor genes (p53 and Rb). Previous studies showed that small-interfering RNAs (siRNAs) targeting the MAPK p42 gene partly inhibit proliferation and increase apoptosis in human cervical carcinoma HeLa cells. Results of a microarray analysis showed that MAPK p42 siRNA inhibited cell growth thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Thus, non-specific effects of MAPK siRNA affecting the expression of other MAPKs are possible. For example, it has been reported that siRNA of p42-MAPK reduced the expression of p42 and simultaneously up-regulated the expression of p38 (Yuan et al 2010). Thus, specific inhibitors of MAPK are helpful tools for exploring the involvement of MAPK, albeit with some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, non-specific effects of MAPK siRNA affecting the expression of other MAPKs are possible. For example, it has been reported that siRNA of p42-MAPK reduced the expression of p42 and simultaneously up-regulated the expression of p38 (Yuan et al 2010). Thus, specific inhibitors of MAPK are helpful tools for exploring the involvement of MAPK, albeit with some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, non‐specific effects of MAPK siRNA affecting the expression of other MAPKs are possible. For example, it has been reported that siRNA of p42‐MAPK reduced the expression of p42 and simultaneously up‐regulated the expression of p38 (Yuan et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the complex process of the regulation of a variety of signalling networks in the development and progression of cervical cancer is of great importance. As one of the key genes promoting apoptosis, tumour protein P53 (p53) serves an important role in controlling the cell cycle, inhibiting tumour formation, maintaining cell genome integrity and responding to various cellular stresses (9)(10)(11)(12). In recent years, accumulating evidence has demonstrated that the p53 protein may translocate from the cytoplasm to the mitochondria and activate mitochondria-related apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%